(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
This article discusses methods and approaches to improving phonetic skills among students learning English for special purposes (ESP – English for Specific Purposes). Special attention is paid to the phonetic difficulties faced by such students, as well as to the specific phonetic requirements that arise in the context of professional communication. The abstract discusses methods that help improve pronunciation, intonation and rhythm of speech, which are necessary for effective communication in specialized fields such as medicine, law, business communication and technical sciences. An important role in learning is given to the integration of phonetics with professionally oriented content, which increases motivation and contributes to the accelerated development of listening and speaking skills